Management of Metastatic Pure Teratoma in Chemotherapy Naive Patients With Testicular Primaries. (October 2020) - Cary, Clint; Kern, Sean Q.; Jacob, Joseph M.; Calaway, Adam C.; Foster, Richard S.; Einhorn, Lawrence H.
Abstract : Introduction: Patients diagnosed with stage II nonseminomatous germ cell tumors (NSGCT) often receive chemotherapy as primary treatment which exposes patients to immediate and long-term risks of chemotherapy. These risks can be avoided by proceeding to primary retroperitoneal lymph node dissection (RPLND) when a high suspicion of pure metastatic teratoma in the retroperitoneum (RP) exists. We propose that all stage II NSGCT patients with pure testicular teratoma, normal serum tumor markers, and with RP cystic metastases on imaging can safely be treated with primary RPLND. Methods: We identified 14 patients found to have 100% teratoma in orchiectomy specimens, negative serum tumor markers, and with metastatic cystic RP disease. Disease recurrence was also evaluated to establish efficacy of treatment. Results: All 14 patients were chemotherapy naive and found to have pure metastatic teratoma. All patients were IGCCCG good risk with stage IIA (21.4%), IIB (35.7%), and IIC (42.9%) disease. Median RP mass size was 4.9 cm (1.8 to 24 cm). All patients underwent a RPLND finding 100% teratoma in the RP. Median follow-up was 6.9 years. One patient (7.1%) who received a right modified template RPLND relapsed in the left RP 10.2 years later who underwent treatment and has been disease free for over 5.5 years. Conclusions: Primary surgical treatment in this cohort of pure metastatic teratoma resulted in good clinical outcomes and the ability to avoid unnecessary induction chemotherapy. It is important that contrary to previous suppositions, patients with pure teratoma of the testis can independently metastasize with teratoma only, without metastatic carcinoma.